Home experiences that foster readiness for learning early mathematical concepts: An exploratory study - Orillosa, Joyce Ferro (Animo Repository, 2012)
Children are best understood in the context of their family, most especially because their experiences from their families affect their learning. Families may be able to provide personal knowledge of the child that may guide the teachers in math instruction and families actually feel supported when included in the planning process of their child's mathematical learning. Personal stories of parents will give light to the following: (1) their current practices at home, (2) the reasons behind these practices, (3) the context of their practices, (4) the implications of their practices. The stories of parents will be able to guide the teaching-learning process in a preschool classroom, most especially with regard to understanding of previous math experiences, strategies in teaching math concepts, planning of math experiences, implementation of math activities based on math experiences, and assessment of math activities. This study aims to explore the context of parent's teaching practices of math concepts, so as to draw implications for basing teaching on prior learning experiences of children. The description will be based on interviews with five pairs of parents.